2009
DOI: 10.1136/qshc.2007.025296
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a standard medication chart on prescribing errors: a before-and-after audit

Abstract: Introduction of a standard revised medication chart significantly reduced the frequency of prescribing errors, improved ADR documentation and decreased the potential risks associated with warfarin management. The standard chart has enabled uniform training in medicine management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 39 publications
4
58
1
Order By: Relevance
“…Over a decade, workers in Brisbane introduced a revised medication chart, audited its before-and-after use in five hospital sites in Queensland (demonstrating a significant fall in prescribing errors) and last year published their analysis of the implementation of their National Inpatient Medication Chart in 22 hospitals nationwide; the prescribing error rate fell by a third. 10,11 While acknowledging a Hawthorn effect -whereby the process of education and implementation may have played a role in reducing error rates in this before-and-after study -the authors comment that the standard format facilitates the education of prescribers, and…”
Section: Rocket Scientists Need Not Applymentioning
confidence: 98%
“…Over a decade, workers in Brisbane introduced a revised medication chart, audited its before-and-after use in five hospital sites in Queensland (demonstrating a significant fall in prescribing errors) and last year published their analysis of the implementation of their National Inpatient Medication Chart in 22 hospitals nationwide; the prescribing error rate fell by a third. 10,11 While acknowledging a Hawthorn effect -whereby the process of education and implementation may have played a role in reducing error rates in this before-and-after study -the authors comment that the standard format facilitates the education of prescribers, and…”
Section: Rocket Scientists Need Not Applymentioning
confidence: 98%
“…Standardisation and the resultant uniformity of practice have been shown locally to reduce prescribing and administration errors, 10 and a pilot study involving insulin administration resulted in a reduction of the frequency of hypoglycaemia. 11 The primary aim of this medication initiative was to improve the safety of insulin prescribing and administration in Queensland public hospitals without adversely affecting blood glucose control. Common errors related to insulin that have previously been documented are listed in Box 1.…”
Section: Quality and Safety Interventionsmentioning
confidence: 99%
“…But multiple designs of cockpits or prescription charts can lead to unnecessary errors, however good the background knowledge is. Though the NHS Chief Pharmacist has not supported UK standardization, research from Australia showed benefits [2]. The variability of the available systems with a lack of minimum standards is a problem.…”
mentioning
confidence: 99%